Effectiveness of a Virtual Exercise Program During COVID-19 Confinement on Blood Pressure Control in Healthy Pregnant Women - Silva-Jose, Cristina; Sánchez-Polán, Miguel; Diaz-Blanco, Ángeles; Coterón, Javier; Barakat, Ruben; Refoyo, Ignacio (Frontiers in Physiology, 2021)
Background: The situation caused by COVID-19 has led to movement restrictions for the majority of the population due to the confinement established by the health authorities. This new situation has changed people's habits and significantly affected the pregnant population. Decreased exercise and increased psychophysical stress are associated with excessive weight gain, diabetes, and gestational cardiovascular complications that affect the mother, fetus, and newborn. Recent research shows that the dynamics of maternal blood pressure is one of the most important control factors during pregnancy. Thus, prevention of these type of pathologies through interventions without maternal-fetal risks is important. Objectives: To examine the influence of a virtual exercise program on maternal blood pressure during pregnancy. Materials and methods: A randomized clinical trial design was used (NCT04563065). Data from seventy-two pregnant women without obstetric contraindications under confinement conditions in the Madrid area were collected. Women were randomly assigned to the intervention (IG) or control group (CG). They previously signed informed consent forms. A moderate exercise program was performed as an intervention from 8-10 to 38-39 weeks of pregnancy. Systolic (SBP) and diastolic (DBP) maternal blood pressure were measured during the first, second and third trimesters of pregnancy, as well as before and immediately after delivery in both study groups. Results: No differences in systolic and diastolic blood pressure during the first, second and third trimesters were found between groups. Significant differences in SBP were found immediately before delivery (IG= 119.83 ± 10.16 vs CG=125.6 ± 10.91; p= 0.047) and immediately after delivery (IG=115.00 ± 11.18 vs CG=122.24 ± 15,71; p= 0.045). Conclusions: Results show lower SBP values for the IG during delivery than CG. A virtual exercise program throughout pregnancy during COVID-19 confinement can help to control systolic blood pressure before and immediately after delivery in healthy pregnant women.